Relationship between Behavioural Empowerment and Employee Commitment in selected Star Rated Hotels in Kisumu City, Kenya - Jumah , Lucy; Nthiga, Rita (Human Resource and Leadership Journal, 2022)
Purpose: The objective of this study was to determine the relationship between behavioural empowerment and employee commitment in selected star-rated Hotels in Kisumu City, Kenya. This study was anchored on Social Cognitive Theory. Methodology: The study adopted explanatory and descriptive research designs. The target population was 1372 non-managerial employees and 130 managerial employees from 34 star rated hotels. A sample size of 310 non-managerial employees and 13 management staff formed the sample for the study. The respondents were selected using stratified and simple random sampling techniques. Questionnaires and interview schedule were used to collect data. The validity of the surveys was established using professional judgment. The dependability of the research tool was assessed using Cronbach's Alpha Coefficient. Both descriptive and inferential statistics were used to analyze the data. Mean, frequencies, and standard deviation were included in descriptive statistics, whereas linear regression was part of inferential statistics and data presented using tables. Findings: According to the study's findings, employee commitment and behavioral empowerment were significantly positively correlated in a few star-rated hotels (1=0.751; p0.05). Unique Contribution to theory, practice and policy: The study came to the conclusion that, in particular hotels, behavioural empowerment had a substantial impact on employees' engagement. Encourage hotel staff to have confidence in their sense of judgment, values, work roles, and actions related to their jobs.